Non-linear fuzzy-PID controller design for track following of hard disk drive servo system - Boonpranchoo, V.; Numsomran, A.; Chaiyasith, P.; Chaoraingern, J.; Tipsuwanporn, V. (My University, 2017)
This paper presents a non-linear control design scheme for track following control of hard disk drive using Fuzzy-PID controller. The proposed scheme, using a parallel structure combined of non-linear Fuzzy PI controller and Fuzzy PD controller, controls the response of a track following control of hard disk drive system to decrease total of non-repeatable position error (NRPE) and position error signal (PES). A performance verification of the proposed controls was also conducted using HDD benchmark simulation system. Results showed that the non-linear Fuzzy PID controller satisfies an acceptable performance in hard disk drive head track following control and effectively robust to disturbance and process parameter perturbations.
Keywords: Fuzzy PID; Hard Disk Drive; Track Following Control